Environments for Imitation: Second-Language Use and Development Through Embodied Participation in Preschool Routine Activities. Issue 1 (2nd January 2021) - Samuelsson, Robin
ABSTRACT: This article examines how the environment and routines within preschools can support second language use and development. It suggests that certain imitable aspects common to Swedish preschools make the environment suitable for L2 use and development. Data build on a qualitative synthesis of two studies from which typical routine activities where children with Swedish as L2 participate are analyzed. It is suggested that properties of the preschool routine activities follow certain interactional patterns and build on imitable cultural scripts that can aid L2 use through embodied participation or nonverbal and verbal interaction. The settings are as such suitable for child participation and can afford L2 development. In children's play, the same cultural patterns and forms of language are used, making them an extension of some routine activities and an important arena to practice cultural knowledge with the developing L2.